The Bible as history - Keller, Werner, 1909-1980.; Rehork, Joachim (New York : Morrow, 1981)
A standard text on biblical investigation, with descriptions of the excavations, the deciphering of ancient documents, and the informed arguments concerning the reliability of the Bible. New techniques have brought much additional information to light; some theories have been confirmed, others badly shaken.
Digging up the Old Testament. The coming of the patriarchs : from Abraham to Jacob ; In the realm of the pharaohs : from Joseph to Moses ; Forty years in the wilderness : from the Nile to the Jordan ; The battle for the Promised Land : from Joshua to Saul ; When Israel was an empire : from David to Solomon ; Two kings--two kingdoms : from Rehoboam to Jehoiachin ; From the Exile to the Maccabean Kingdom : from Ezekiel to John Hyrcanus -- Digging up the New Testament. Jesus of Nazareth ; In the days of the apostles.
Translation of Und die Bibel hat doch recht.
Includes bibliographical references (p. 394-398) and index.
Keywords: Bible -- History of contemporary events; Bible -- Antiquities; Bible History; Biblical Archaelogy; Israel -- History of; Inter-Testamental period; New Testament history